Persepsi Masyarakat Pesisir Pantai Desa Reroroja Dalam Pemanfaatan Ekosistem Mangrove Sebagai Ekowisata - Mulyawati, Indah; Fitriah Fitriah; Yuliana Dua Solo (Journal Innovation In Education, 2024)
This study aims to determine the perceptions of coastal communities in Reroroja Village in the Utilization of mangrove ecosystem as ecotourism. This study used a qualitative descriptive approach. There were 3 data collection techniques used, namely observation, interviews, and documentation. In this study there were 12 informants consisting of the mangrove forest manager, the Head of Reroroja Village, Kena RT Dusun Magelo’o, and people from Magelo’o of Magepanda District, Sikka Regency. Based on the results of the study, it can be cancluded that the perception of the people of Reroroja Village in utilizing mangrove forests as an ecotourism area is still relatively low. This is caused by the lack participation og the village community in protecting and managing mangrove forests as ecotourism. Factors that influence community perceptions are knowledge, attitudes and level of education. The community considers thet protecting the mangrove forests area in Reroroja Village in not their reponsibility but that it is already the responsibility of the management.